Factors Affecting Compliance With Infection Prevention And Control Standard Precautions Among Healthcare Workers In Makkah, Saudi Arabia - Abu Rabiah Abdulrahman Sulaiman A, Sultan Saeed Matrok Aldhahri, Raed Muhaysin Alobaid Alotaibi, Rasha Mubarak Alhassan Alhindi, ‏Ahmad Saadi Alzahrani, Muath Saleh algathlan, Ahmed Abdulaziz Abdulrhman Bindraihim; Majid Mubarak Alosaimi, Yahya Ali Hassan Mubaraki, Khalaf Abdullah Matar Al-Otaibi, Hamdan Ayad Alotaibi, Abdullah Abdul Rahman Al Qasim (Migration Letters, 2022)
Background: Compliance with infection prevention and control standard precautions (IPCSPs) remains a major challenge in many countries including Tanzania. Lack of compliance exposes healthcare workers (HCWs) and patients to a high risk of developing healthcare-associated infections (HAIs) including antimicrobial-resistant microorganisms which can contribute to the spread of antimicrobial resistance (AMR). This study investigated compliance with IPCSPs and associated factors among HCWs in public healthcare facilities (HFs) in Makkah, Saudi Arabia between January and March 2022. Methods: A cross-sectional study was conducted involved 400 HCWs from difference healthcare facilities (HFs) including hospital, and health centres. The Compliance with Standard Precautions scale (CSPS) tool developed by WHO was used. Descriptive and modified Poisson regression analysis was done. A P-value of less than 0.05 indicated statistical significance. Results: Only 22.5% (90/400) of HCWs had high compliance (above 80%) to IPCSPs. The majority of HCWs reported highest compliance on discarding used needles/sharps into sharps containers (94%), the lowest IPCSPs compliance was for the correct handling of spills, taking a shower after extensive splashing and not re-using disposable masks, 8%, 28.5% and 34% respectively. Attending IPC training or an IPC seminar in the p[1]revious year (ARR¼2.97 [1.87e4.72] P<0.001), the number of years of work experience (ARR¼2.08[1.22e3.54] P¼0.007), and having experienced a needlestick injury (ARR¼0.62 [0.40 e0.95] P¼0.028), were identified as predictors of HCWs compliance with IPCSPs. Conclusion: The majority of HCWs in Makkah region had low compliance with IPCSPs according to national standards. IPC training and the number of years of work experience predicted high compliance with IPCSPs. Capacity building initiatives, mentorship and supportive supervision should be emphasised for all HCWs in all HFs.